2021
DOI: 10.3389/fphar.2021.726199
|View full text |Cite
|
Sign up to set email alerts
|

Anticholesterolemic Activity of Three Vegetal Extracts (Artichoke, Caigua, and Fenugreek) and Their Unique Blend

Abstract: Hepatic-related diseases, in particular hyperlipidemia and hypercholesterolemia, are a thorn on the side of the national health institutes around the globe. Indeed, liver lipid and cholesterol dysregulation could lead to atherosclerotic plaque formation and cardiovascular diseases. Currently, statin administration and monacolin K consumption are the main therapies proposed to counter this alarming connection, but relevant side effects are known. To overcome this issue, safe nutraceutical formulations and/or ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Furthermore, these cells maintain the ability to express the main enzymes that regulate the metabolism of hepatic, plasma, and biliary cholesterol and appear to be able to synthesize and secrete bile acids. These activities respond consistently to what is known about human cholesterol metabolism [ 24 ]. For this reason, this cellular model was applied in this study to verify the safety and efficacy of a new combination of various natural ingredients with RYR in order to create the basis for a new therapeutic strategy for humans.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…Furthermore, these cells maintain the ability to express the main enzymes that regulate the metabolism of hepatic, plasma, and biliary cholesterol and appear to be able to synthesize and secrete bile acids. These activities respond consistently to what is known about human cholesterol metabolism [ 24 ]. For this reason, this cellular model was applied in this study to verify the safety and efficacy of a new combination of various natural ingredients with RYR in order to create the basis for a new therapeutic strategy for humans.…”
Section: Introductionmentioning
confidence: 64%
“…In this context, this is the first study that investigates the anti-cholesterol activity of a new formulation, called Esterol10 ® , obtained by combining Salvia Extract 10 µM, Quercetin 10 µM, Vitamin D3 1 nM, Vitamin K2 1 µM, CoQ10 1 µM, Resveratrol 1 µM, 9 nM astaxanthin, 1 µM sodium selenite, 1 µM folic acid and 1 µM RYR in an in vitro study. Indeed, when mixed together, the three extracts proved to be more effective than RYR in promoting the lowering of cholesterol in hepatocytes, through a reduction in the synthesis of cholesterol and its conversion into bile acids through the choleresis process which is a complex biochemical process that leads to the production of bile, an iso-osmotic electrolyte solution that forms in the liver as a product of its secretory function [ 24 ]. Taken together, these results demonstrated that Esterol10 ® significantly improves hepatic metabolism by regulating the synthesis of cholesterol through the improvement of HMGCoA reductase and the reduction of its receptor expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations